2007
DOI: 10.1002/bjs.5793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various POSSUM models for predicting mortality in patients undergoing elective oesophagectomy for carcinoma

Abstract: P-POSSUM provided the most accurate prediction of in-hospital mortality in this group of patients who had elective oesophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…A number of predictive models for postoperative morbidity and mortality after esophagectomy have been developed, focusing primarily on fixed, preoperative risk factors [23][24][25][26][27][28][29] ; however, attempts to validate these risk stratification tools externally have demonstrated limited clinical applicability. 7,30-32 A recent systematic review of 20 clinical prediction models for mortality after esophagectomy concluded that these models were unreliable because of poor discrimination and inadequate validation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of predictive models for postoperative morbidity and mortality after esophagectomy have been developed, focusing primarily on fixed, preoperative risk factors [23][24][25][26][27][28][29] ; however, attempts to validate these risk stratification tools externally have demonstrated limited clinical applicability. 7,30-32 A recent systematic review of 20 clinical prediction models for mortality after esophagectomy concluded that these models were unreliable because of poor discrimination and inadequate validation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, POSSUM has been proposed as a predictor equation taking into account differences in case-mix [6][7][8][9]. However, POSSUM requires up to 19 perioperative physiological parameters, including some parameters that are not routinely examined before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting postoperative mortality and risk assessment before surgery continues to be challenging [6,7]. In patients undergoing elective esophagectomy for esophageal cancer, the Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (POSSUM) has been reported to predict mortality accurately [8,9]. However, POSSUM requires up to 19 perioperative physiological variables, which are not necessarily collected as a part of routine clinical care [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 545 patients who underwent esophagectomy in public hospitals in Hong Kong, the observed in-hospital mortality rate was 5.5%, whereas that predicted by Portsmouth (P)-POSSUM score was 4.7%. P-POSSUM also showed no lack of fi t, and the area under the receiver operator characteristic curve (ROC) was 0.776, demonstrating good discriminatory power [9]. It is uncertain if patient selection based on a strict mathematical scoring system is better than one based on surgeons and anesthesiologists' assessments alone.…”
Section: Short-term Prognosticationmentioning
confidence: 97%